The Fourth Little Pig - Celsi, Teresa Noel; Cushman, Doug (Milwaukee : Raintree Publishers, 1990)
The sister of the Three Little Pigs comes to visit and tries to persuade her brothers, who have been hermits since an episode with a wolf, to overcome their fears and go outside.